Síntese e caracterização estrutural e biológica de vidros bioativos com capacidade de liberação controlada de íons metálicos Mn e Co com potencial efeito terapêutico osteogênico e angiogênico para aplicações na engenharia de tecidos - Breno Rocha Barrioni (2018)
Bioactive glasses are outstanding materials in tissue engineering due to their high bioactivity and biocompatibility. Different bioactive glass compositions can be obtained by the sol-gel process, and their structure allows the incorporation of various concentrations of different ions with physiological activities and therapeutic properties. Those ions are released during the dissolution process of the material, improving its performance. Among the different ions with therapeutical properties, manganese has been shown to enhance cell adhesion, growth and proliferation of osteoblasts, while cobalt is a known angiogenic agent. In this context, this work reports the development of new bioactive glass compositions derived from the sol-gel process, containing manganese or cobalt in their structure, as potential therapeutic metallic ions. The influence of the incorporation of different concentrations of these ions on the structure and properties of the bioactive glasses was evaluated. Bioactive glass microparticles containing Mn and Co with controlled ion release capability in physiological medium were obtained. Structural evaluation confirmed the presence of Mn2+ in the structure of bioactive glasses, while Co2+ were mostly observed in the glasses containing this ion, although the use of different precursors has been shown to affect the structure of these materials, with the presence of Co3+ species when cobalt chloride was used as precursor. The viability of cells exposed to different concentrations of the bioactive glasses ionic product was confirmed. Bioactive glasses containing Mn demonstrated ability to stimulate all stages of differentiation of mesenchymal stem cells derived from human bone marrow and subsequent mineralization, confirming their role in enhancing bone regeneration. The morphological and histological studies performed after the implantation of bioactive glasses containing Co in rats demonstrated that there was no induction of adverse responses, and the presence of inflammatory infiltrate and neoformed vessels are indicative of a high level of angiogenesis in the material. The incorporation of Mn and Co in bioactive glasses has proved to be a potential strategy to improve its potential for tissue engineering.